Scope of Service-Learning in Accomplishing Objectives of National Education Policy 2020, India - A Conceptual Analysis - Dustker, Srinivas; Bandi, Surendra; Oakes, William (Journal of Engineering Education Transformations, 2025)
National Education Policy (NEP) 2020 is the latest evolution of the Indian Education System built on the foundational pillars of Access, Equity, Quality, Affordability and Accountability. The NEP focuses on providing quality education to all students, irrespective of their socio-economic background or place of residence, thus cultivating the youths of tomorrow into moral and civil citizens leading to the development of the nation. The NEP also encourages education to be Holistic, Integrated, Enjoyable and Engaging, which can be achieved by introducing and integrating new pedagogies. Service-learning is one such pedagogy that aims at being experiential, inquiry-driven, and meaningful. Service-learning is popular at enabling students to apply classroom learnings into the real-world and gain hands-on experience, because of which, it is widely integrated into Higher Education Institutions (HEIs), especially at the undergraduate level, around the world. Given the outcome of implementing NEP by 2030, it is reasonable to envision HEIs of India, primarily engineering, to adopt and integrate service-learning experiences into their curriculum as well. This paper is an attempt to showcase the learning outcomes and scope of service-learning as a pedagogy to accomplish the objectives of NEP 2020.